Geological Structural Surface Evaluation Model Based on Unascertained Measure - Kang Zhao; Qing Wang; Yajing Yan; Junqiang Wang; Kui Zhao; Shuai Cao; Yongjun Zhang (Geofluids)
The surrounding rock structure plane survey is the basis for mine geological structure evaluation and stability of surrounding rock. On the basis of the unascertained measurement theory and scanline method, the surrounding rock stability of the underground geological structure plane in Lingbao Luoshan Gold Mine is evaluated. First, according to the structural plane five grading standards, the 9 single-index measure functions are constructed. Second, the information entropy is used to determine the weight of each indicator. Accordingly, a multi-index comprehensive measure evaluation vector is established. Finally, the confidence level is used to determine the structural plane stability level. Results show that surrounding rock grades of middle sections of R1, R2, and R3 are Grades III, IV, and IV in Lingbao Luoshan Gold Mine, respectively. The evaluation grade is consistent with the actual situation of the mine, and strengthening the surrounding rock support for the middle sections of R2 and R3 is necessary. According to engineering practice, the evaluation model of the underground structure of metal mines established in this study has a practical value.